Relationship between Anthropometric Characteristics with Social Physique Anxiety among Alzahra University Staff - Parvaneh Nazarali; Azam Ramezankhani (Iranian Association of Health Education and Health Promotion, 2017)
Background and objective: Obesity is one of the problems that threaten the public health. The aim of this study was to investigate the relationship between anthropometric characteristics with social physique anxiety (SPA) in Alzahra University Staff. Materials and methods: In this cross-sectional study, 135 female staff of Alzahra University participated in this study. Motl and Conroy 7-item Social physique questionnaire was used in this study. Anthropometric characteristics were assessed with Body Analyzer. Data was analyzed with Pearson correlation using SPSS16 (p < 0.05). Results: Pearson correlation showed a significant positive correlation between body weight, body mass index (BMI), waist circumference, hip circumference, waist-hip ratio (WHR), body fat mass with social physique anxiety.   Conclusion: There was a positive relationship between anthropometric characteristics with social physique anxiety among Alzahra University Staff. Therefore, obesity is considered an important factor in increasing social physique anxiety. Paper Type: Research Article.